Writing Abstract and Keywords of Scientific Article-Do’s and Don’ts (Advancements in Homeopathic Research, 2022)
Background: Writing manuscript is important in any  discipline for the dissemination of new knowledge.  Abstract and keywords are one of the most important  parts of manuscript an editor or a reader looks for as  it gives important points of whole paper as summary.  Hence, knowledge on how to write a good abstract  and keywords is a basic requirement for the authors  to get their paper accepted, well indexed and good  readability. In this paper, we review the literature as  to how to write an abstract and keywords of scientific  articles. Methods: Literature regarding writing abstract, as  well as keywords of scientific articles was searched in  the leading search engine Pubmed with the following  search terms and their combinations: writing abstract,  keywords, scientific article.  Results: After different types of search, fifteen papers  were selected based on their relevancy.  Conclusion:Effective abstracts and keywords provide  sufficient details of the whole paper without looking  or reading the entire article saving a lot of time. This  paper covers various aspects of writing abstract and  keywordsof scientific article.
Keywords: Writing; Scientific article; Abstract; Do’s and Don’ts